2008
DOI: 10.7589/0090-3558-44.4.837
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for an Outbreak of Leptospirosis in California Sea Lions (Zalophus Californianus) in California, 2004

Abstract: ABSTRACT:Leptospirosis has been reported in California sea lions (Zalophus californianus) since 1970; however, the source of infection and mode of transmission remain unknown. To elucidate these features, demographic and environmental risk factors for leptospirosis were evaluated. California sea lion stranding records from northern California for 2004 were used to identify cases of leptospirosis (n5316) and controls (n5143). Demographic characteristics (age class, sex) and environmental factors, representing s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 20 publications
0
13
0
4
Order By: Relevance
“…Male animals in this study were found more likely to carry or shed leptospires than females. A similar trend in male dogs was attributed to roaming (Ward, Guptill, Prahl, Ching Wu, ) and in sea lions, to the more migratory activity of males (Norman, DiGiacomo, Gulland, Meschke, & Lowry, ). Either way, chances of males getting into contact with Leptospira contaminated sources increase consequently.…”
Section: Discussionmentioning
confidence: 56%
“…Male animals in this study were found more likely to carry or shed leptospires than females. A similar trend in male dogs was attributed to roaming (Ward, Guptill, Prahl, Ching Wu, ) and in sea lions, to the more migratory activity of males (Norman, DiGiacomo, Gulland, Meschke, & Lowry, ). Either way, chances of males getting into contact with Leptospira contaminated sources increase consequently.…”
Section: Discussionmentioning
confidence: 56%
“…A leptospirose e brucelose são zoonoses de ampla distribuição, com grande importância econômica e relevância para a saúde pública e saúde animal (FAINE et al, 1999 abortus (DIERAUF et al, 1985;RHYAN et al, 1994;NORMAN et al, 2008;SZONYI et al, 2011). MORGAN, 1984;FOSTER et al, 2007;SCHOLZ et al, 2008SCHOLZ et al, , 2010SCHOLZ et al, , 2016WHATMORE et al, 2014 , 2006).…”
Section: Introductionunclassified
“…Os testes sorológicos são amplamente utilizados para a determinação da prevalência de doenças em populações de animais domésticos e selvagens (BENDER e HALL, 1996) (GAGE et al, 1993;GULLAND et al, 1996;WHITEHOUSE et al, 2003;STAMPER et al, 1998;NORMAN et al, 2008) No INPA os peixes-bois adultos são mantidos em três tanques de 10 metros de diâmetro e 2,7 metros de profundidade e os jovens em tanques de fibra de vidro com 4,5 metros de comprimento por 2,7 metros de largura e 1,1 metros de profundidade (Figura 4). No CPPMA os peixes-bois adultos são mantidos em tanques de dez metros de diâmetro e com 3,2 metros de profundidade e os jovens em tanques de cimento de 4,5 metros de comprimento por 2,7 metros de largura e 1,1 metros de profundidade (Figura 5…”
unclassified
“…Apesar da baixa prevalência, reações positivas a este importante sorovar também foram identificadas nos peixes-bois analisados. Dos resultados da SAM encontrados neste estudo o Patoc, saprófita, foi o mais freqüente, discordando de estudos realizados com pinípedes e cetáceos marinhos, nos quais foi descrito o sorovar Pomona como o mais freqüente e o principal responsável pelos casos clínicos nestes animais, seguido pelos sorovares, Grippotyphosa, Hardjo, Icterohaemorraghiae e Canicola(COLAGROOS et al, 2002; WHITENHOUSE et al, 2003;COLEGROVE et al, 2005;MACKERETH et al, 2005;NORMAN et al, 2008), entretanto nenhum desses estudos foi efetuada em animais da região estudada.O encontro do sorovar Patoc, saprofita, apesar de não patogênico, pois não possui poder de colonização e penetração (JOHNSON e HARRIS, 1976; CULLEN; HAAKE; ADLER, 2004), é de grande importância epidemiológica uma vez que, apesar de raro, já foi isolado de casos clínicos em outras espécies animais(CARROL e LECLAIR, 1969;COMBIESCU et al, 1958).Da quantidade aproximada de 250 leptospiras existentes, a coleção do VPS, uma das mais importantes do país, possui 20 sorogrupos com pelo menos um sorovar de cada grupo já descrito. Sorovares pertencentes ao mesmo sorogrupo podem apresentar reação cruzada na sorologia entre eles, considerando-se o mais provável sorovar, o responsável pela infecção, aquele com os mais altos títulos de anticorpos na reação.…”
unclassified
See 1 more Smart Citation